The prevalence of anxiety, depression and co-dependence among spouses of male patients with alcohol dependence syndrome at a tertiary care hospital in Nepal: A cross-sectional study (Journal of Psychiatrists' Association of Nepal, 2025)
Introduction: Excessive use of alcohol is a major public health concern worldwide. Alcohol dependence is a constant source of stress for the families of alcohol users with dependence and makes them more vulnerable to psychological problems such as depression, anxiety and co-dependence. This study explores the prevalence of anxiety, depression and co-dependence among spouses of male patients with alcohol dependence syndrome.Methodology: A cross-sectional study was conducted among 93 spouses of male patients with alcohol dependence syndrome seeking treatment at the Department of Psychiatry, Tribhuvan University from November 2020 to October 2021. A semi-structured clinical proforma was used to collect data and a validated Nepali version of Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depression. ICD-10 DCR and the Spann-Fischer Codependency Scale were employed to categorize anxiety disorders and depressive disorders and to assess codependence, respectivelyResults: The prevalence of anxiety disorders and depressive disorders were 33.3% and 19.4% respectively. The most common type of anxiety disorder was generalized anxiety disorder (12.9%), and most had mild depressive episodes (10.8%). Codependency was found in all the participants with 65.6% medium codependency and 34.4% high codependency. Both anxiety disorders and depressive disorders were positively correlated with the level of codependence (p < 0.05).Conclusion: A significant proportion of spouses of male patients with alcohol dependence syndrome suffer from anxiety and depression and have high codependence. The findings emphasize the need for integrated mental health, family support and counselling interventions for the spouses of male patients with alcohol dependence syndrome.